Pembuatan Sistem Informasi Pengelolaan Laboratorium (SIMPAL) Menggunakan Borland Delphi 7.0 - Imron Rosadi; T Takim (Jurnal Pengelolaan Laboratorium Pendidikan, 2023)
The management of the survey and mapping laboratory at the Civil Engineering Department of the State Polytechnic of Malang so far were used the conventional method, recording stock of equipment and materials supplies and the process of borrowing and returning equipment is done by filling out work papers or forms that are quite a lot so the process is quite time-consuming. The purpose of this research is to create a laboratory management information system using the Delphi 7.0 program, it is hoped that laboratory management that is integrated with computers can make laboratory activities more effective and efficient. By using the research and development (R&D) method, the following research results were obtained: a) a database system that can accommodate the recording of all laboratory management activities; b) software as an interface between laboratory users and the database system. From the series of research that has been carried out, it can be concluded that with an information system that has made service activities in the survey and mapping laboratory more effectively and efficiently.